The effect of innovation on employment: Mexico and Ecuador - Vergara Reyes, Delia Margarita; Guerrero, Alex J.; Arenas Díaz, Guillermo; Heijs, Joost (Estudios de Economía, 2023)
This work provides evidence of the effect of innovation on employment in two countries where this impact has not been previously analysed: Mexico and Ecuador. Following the method proposed by Harrison et al. (2014), we find that introducing new products in the market positively affects employment in Mexico and Ecuador. While process innovation tends to destroy jobs in Mexico, it has no effect in the case of Ecuador. The positive impact of product innovation is observed to be greater than the loss of employment caused by process innovation.